2005
DOI: 10.4141/p03-065
|View full text |Cite
|
Sign up to set email alerts
|

Compositional changes over four years for binary mixtures of grass species grown with white clover

Abstract: 2005. Compositional changes over four years for binary mixtures of grass species grown with white clover. Can. J. Plant Sci. 85: 351-360. Kentucky bluegrass, meadow fescue, orchardgrass, tall fescue, timothy, and reed canarygrass were seeded in all possible two-grass combinations with white clover in conventional and underseeded barley treatments using a split-plot design at the Western Agriculture Centre near Pynn's Brook, NL. The objectives were: (1) to assess dry matter yield (DMY) of two binary grass speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In a study conducted in Québec where white clover was grown in a mixture with either meadow fescue or meadow bromegrass under frequent cutting (Drapeau and Bélanger 2009), the proportion of white clover decreased from the first to the third post-seeding year, reaching values below 10%. In a study of white clover in mixtures with grasses conducted in Newfoundland, the proportion of white clover also decreased from 40% in the first postseeding year to 27% in the third post-seeding year (McKenzie et al 2005). White clover in mixtures with forage grasses is, therefore, not well adapted to frequent cutting or rotational grazing under the conditions of eastern Canada.…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted in Québec where white clover was grown in a mixture with either meadow fescue or meadow bromegrass under frequent cutting (Drapeau and Bélanger 2009), the proportion of white clover decreased from the first to the third post-seeding year, reaching values below 10%. In a study of white clover in mixtures with grasses conducted in Newfoundland, the proportion of white clover also decreased from 40% in the first postseeding year to 27% in the third post-seeding year (McKenzie et al 2005). White clover in mixtures with forage grasses is, therefore, not well adapted to frequent cutting or rotational grazing under the conditions of eastern Canada.…”
Section: Resultsmentioning
confidence: 99%
“…These imbalances and the associated nitrate leaching may be mitigated by establishing mixtures of grass species in legume-based pastures. Mixtures of grass species grown with clover have been shown to increase and sustain herbage production throughout the growing season compared with pastures dominated by a single grass species (McKenzie et al 2005;Kunelius et al 2006). The capacity of variable mixtures of grass species, grown with clover, to contain the seasonal accumulation of nitrate in the soil and the associated risk of nitrate leaching should, however, be tested experimentally.…”
Section: Pasture Managementmentioning
confidence: 99%
“…Consequently, pastures with increased plant species diversity could improve forage yield and yield stability. In studies conducted in Atlantic Canada, more complex mixtures were shown to result in more resilient pastures that were ultimately more productive (McKenzie et al 2005;McElroy et al 2012;Papadopoulos et al 2012).…”
Section: Introductionmentioning
confidence: 99%